Valorisation of Deinking Paper Sludge for Fertiliser Purposes: New Perspective in Sustainable Agriculture - Halyna Kominko; Katarzyna Gorazda; Katarzyna Łoś; Zbigniew Wzorek (Agronomy)
The growth of the global population, coupled with concomitant economic development, has resulted in the generation of a substantial quantity of waste. The transition of the European Union’s economy towards a closed-loop model is prompting a comprehensive search for waste management concepts across a range of industrial sectors. The objective of this study is to valorise deinking paper sludge, which has a high potential for soil formation due to its high organic matter content. To produce organic–mineral fertiliser, the deinking sludge was subjected to acid hydrolysis, then neutralised with KOH solution and enriched with poultry litter ash. The final products were characterised in terms of their nutrient and heavy metal content. The bioavailability of phosphorus, along with the forms in which it occurs in fertilisers, was determined through the implementation of a five-step fractionation procedure. Furthermore, an eight-week incubation period was conducted to assess the fertilisers’ performance in soil. Soil samples were tested on a weekly basis for pH, water-soluble and bioavailable phosphorus content using the spectroscopic method after previous extraction in water and Bray’s solution, and catalase activity using the titrimetric method. The resulting fertilisers were found to meet the requirements for organo-mineral fertilisers and were categorised as PK-type fertilisers with a total nutrient content of 24.6–39.3%. Fractionation studies demonstrated that the fertilisers contained 20–30% of the total potentially bioavailable phosphorus. Furthermore, the long-term release of phosphorus from the fertilisers was confirmed through incubation studies. Additionally, the fertilisers were observed to contribute to an increase in catalase activity in the soil.